Modelo preditivo de fraude ocupacional nas organizações privadas - Santos, Renato de Almeida dos (2016)
Fraud is a complex phenomenon and often systemic in its nature, being, therefore, difficult to strive against it. The studies and researches are in the field of enterprise studies, the base to identify the causes of defrauders’ behaviour. The aim of the thesis is the elaboration of a predictive model of frauds in private enterprises. The methodology—multiple case studies—structured the qualitative analysis of secondary data provided by S2 Consultoria, a Brazilian company. The fifteen interviews, purposefully selected, were carried out during the processes of verification of fraud in ten enterprises in Brazil, and all interviewees confessed practicing fraud in the enterprises where they worked. The research showed the influence of the contingencies surrounding the defrauders and individual differences related to the elements that motivated them to act as such. If individuals commit fraud by the influence of these contingencies, as varied as they can be, then there is an encouraging prognostic: It is possible not only to prevent it, in the sense of increasing the efficacy of the proceedings to deal with fraud, but there is also the possibility of a relative prediction concerning the formation of the agent. The model— named “pentagon of fraud”—is a proposal whose aim is to present preventive strategies